(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In the article guides the institutional and political analysis of theoretical, methodological and practical problems in the field of personnel policy, legal and institutional regulation in the law enforcement system, reveals the peculiarities of formation of personnel policy in the present conditions of the government; define the content and prospects of development of the modernization of the law enforcement system in Kazakhstan. The proving necessity of modernization of the law enforcement system and the new model of statehood ¬ personnel policy in law enforcement departments of the Republic of Kazakhstan , which should be contribute to the effectiveness of political power and control of the state in order to provide innovative, democratic development of Kazakhstan’s society . Explore more factual material, examined the experience of practice in reforming the law enforcement system, put into analysis of effective approaches forms and methods, marked the factors influencing on the optimization of the system of personnel work in law enforcement. On the basis of these results developed the methodological basis of the concept of law enforcement personnel policy of the Republic of Kazakhstan. Key words: state personnel policy, modernization of the law enforcement system, the model of the state personnel in law enforcement.